Combinations and loads of bacteria affect the cytokine production by fetal membranes: An in vitro study - Noda-Nicolau, Nathalia Mayumi [UNESP]; Polettini, Jossimara [UNESP]; Peltier, Morgan R.; da Silva, Márcia Guimarães [UNESP]; Menon, Ramkumar (Wiley, 2016)
Problem: The polybacterial invasion and inflammation of the amniotic cavity is a common scenario in PTB, and then, we analyzed the cytokine production by human fetal membranes to better understand the host response to polybacterial infections. Method of study: Fetal membranes were treated by heat-inactivated genital mycoplasmas and Gardnerella vaginalis at 103 or 106 colony/color-forming units/mL alone or in combination. Cytokines/receptors were measured in the medium by immunoassays. Results: Stimulation of genital mycoplasmas did not increase the proinflammatory cytokines, except Ureaplasma urealyticum that increased IL-8 levels. However, U. urealyticum and Mycoplasma hominis significantly increased IL-10 and IL-13 levels. G. vaginalis alone or in combination with genital mycoplasmas showed an increased proinflammatory and anti-inflammatory cytokines. Conclusions: G. vaginalis sustain a proinflammatory response in the fetal membranes in vitro, while genital mycoplasmas induce a strong control of the inflammatory response. The ability of genital mycoplasmas to control the proinflammatory response may favor their survival in the upper genital tract.
Keywords: Gardnerella vaginalis; genital mycoplasmas; polybacterial infection